Research and development of a composite with transparent polypropene fiber Part I: a study of combining the Taguchi method with the analytic hierarchy process for masterbatch modification and toughening to enhance characteristics. Issue 3 (February 2019) - Kuo, Chung-Feng Jeffrey; Huang, Chang-Chiun; Ting, Cheng-Hsiang; Dong, Min-Yan; Lan, Wei Lun
Polypropene (PP) has weak mechanical properties; relevant fibrous composite products are likely to bend under stress, becoming unavailable due to creases and folds. In order to maintain the product haze and tensile characteristic, the toughening property is enhanced greatly in this study. Firstly, the PP and enhanced rubber segment-styrene ethylene/butylene styrene (ERS-SEBS) are analyzed, and the two materials' melting points and cracking points are confirmed. Three proportions of composite are made by single-screw mixing. The cost is reduced and the efficiency is confirmed by the Taguchi experiment. The single quality optimum combination is obtained by analysis of variance (ANOVA) and a factor response table. The optimum process parameters are designed according to the contribution degrees of quality weight and control parameters by using the analytic hierarchy process and ANOVA of the Taguchi method based on the reproducibility of the single quality optimum combination validation experiment. According to practical validation, in the ERS-SEBS modified optimum process of PP, the impact strength is 7.26 kJ/m 2, higher than that of regular PP by 142%. The tensile strength is 23.69 MPa, high than that of regular PP by 3%. The haze can be reduced to 5.7%. The developed composite of the PP/styrene triblock copolymer has better mechanical properties and retains its optical performance. It can be used in a fibrous composite to make a composite with transparent fiber to present the fiber line distribution of fabric in the composite.